Biometria e qualidade de frutas nativas da Floresta Atlântica com potencial socioeconômico e ambiental - Barros, Bruna Lara Alvarenga (2019)
The Atlantic Forest is an ecosystem with high biodiversity, rich in fruit species with socioeconomic and environmental potential. Aiming to increase the knowledge about the properties and potentialities of these fruits, the objective was to evaluate the in natura quality of the fruits of araçá-una (Psidium myrtoides O. Berg), cabeludinha (Myrciaria glazioviana), grumixama (Eugenia brasiliensis L.), jabuticaba (Plinia cauliflora), jussara (Euterpe edulis Mart.) and uvaia (Eugenia pyriformis C.), regarding their physicochemical and morphological aspects, encouraging forest conservation through the use of these species. Therefore, the dissertation was developed in two chapters. In the first chapter, it was evaluated the interaction between the three ripening stages and two postharvest times in the physicochemical characteristics of fruits of araçá-una and grumixama, collected in the same environment of occurrence. The fruits of araçá-una harvested at stage 2 and stored for 48h were superior in quality to those harvested at stage 1 and were similar to fruits harvested at maturity stage 3 and stored under the same conditions. Grumixama fruits harvested at stage 3 had higher quality than fruits harvested at other stages, however, storage for 48h under ambient conditions for this stage is not indicated due to the perishability of these fruits. In the second chapter, the objective was to perform the phenotypic characterization of fruits of accesses of araçá-una, jabuticabeira, cabeludinha, jussara and uvaia collected in the montain region of the state of Espirito Santo, through morphoagroanomic descriptors, correlations and genetic parameters. The results indicated that the species have fruits with wide phenotypic variability in size and yield in fruit pulp. The correlations between the biometric characteristics of the fruits demonstrated the potential of this tool for selection of indirect variables for breeding programs, reducing the evaluation time. Most of the observed variability is genetic in nature, indicating potential for genetic gain through selection